A new genus of the tribe Issini Spinola (Hemiptera: Fulgoroidea: Issidae) from China - Che, Yanli; Zhang, Yalin; Wang, Yinglun (Zootaxa, 2011)
Pseudochoutagus curvativus, a new genus and species of Issidae (Hemiptera) is described based on specimens from Hainan, China. The genus is compared to the superficially similar genus Choutagus Zhang, Wang and Che.